As transformações socioespaciais de Frutal MG - Silva, Adriano Reis de Paula e (2012)
This work s purpose is to understand the spatial organization and dynamics of Frutal (MG), a small town that has been going through great economic dynamism throughout the last years and, therefore, socio-spatial changes. At first, Brazil s urbanization process is approached as well as the importance of small cities and the transformations, above all, within the ambit of centrality, that is to say, concerning the influence of the power of polarization and/or leadership from defined spaces due to their concentration of specific elements. Historically, it is presented Frutal s genesis, its development in the economic, demographic and socio-spatial areas and its insertion into regional context. At last, some analysis variables are taken into consideration, such as the county s economic activities, specially those related to agribusiness, which allowed us to understand the connection between their development and Frutal s urban and consequently, interurban dynamics. Finally, this paper helps us to understand the role of social agents in this county s socio-spatial transformations, of which reflections are also noticeable in the urban range. From this work, some tendencies are indicated to Frutal s county and its micro-region.